Violence in the context of new information technologies: The crime of sexual harassment - Alcalá Molina, Félix Andrés (2022)
The purpose of this article is to describe the violence in the context of new information technologies: the crime of sexual harassment. In this regard, the internet has allowed mankind to develop new facets and to communicate using the social media, an authentic revolution for society as a whole. From the time that the Peruvian Government ordered mandatory social distancing as a result of the COVID-19 pandemic, the cyber criminals, pedophiles and stalkers obtained a great advantage to perpetrate crimes. At present, the worldwide violence in all its forms is considered a public health problem, and cyberstalking has become a new form of psychological violence that causes stress, humiliation, anxiety and depression in the most vulnerable population.